Uncertainty, Market Structure, and Performance: The Galbraith-Caves Hypothesis and Managerial Motives in Banking - Edwards, Franklin R.; Heggestad, Arnold A. (Quarterly Journal of Economics, 1973)
I. The market structure-uncertainty avoidance relationship, 455. — II. Rationale behind the Galbraith-Caves hypothesis, 456. — III. A measure of uncertainty avoidance and the theory of the firm under uncertainty, 458. — IV. The Galbraith-Caves thesis in the context of the firm under uncertainty, 460. — V. Testing the relationship between market power and uncertainty-avoidance behavior, 463. — VI. Empirical results, 469. — VII. Conclusion, 472.